2018
DOI: 10.3389/fpls.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Nickel Deficiency? Nickel Fertilization via Soil Improves Nitrogen Metabolism and Grain Yield in Soybean Genotypes

Abstract: Nickel (Ni)—a component of urease and hydrogenase—was the latest nutrient to be recognized as an essential element for plants. However, to date there are no records of Ni deficiency for annual species cultivated under field conditions, possibly because of the non-appearance of obvious and distinctive symptoms, i.e., a hidden (or latent) deficiency. Soybean, a crop cultivated on soils poor in extractable Ni, has a high dependence on biological nitrogen fixation (BNF), in which Ni plays a key role. Thus, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 61 publications
3
26
0
Order By: Relevance
“…Nitrogen fixation by legume forages may be limited by molybdenum deficiency (e.g., Bell et al 1990). There have been no studies in Cambodia or Laos to determine the sufficiency of cobalt (Bell and Dell 2008) or nickel for symbiotic nitrogen fixation in legume forages (Freitas et al 2018).…”
Section: Management Of Soil Nutritionmentioning
confidence: 99%
“…Nitrogen fixation by legume forages may be limited by molybdenum deficiency (e.g., Bell et al 1990). There have been no studies in Cambodia or Laos to determine the sufficiency of cobalt (Bell and Dell 2008) or nickel for symbiotic nitrogen fixation in legume forages (Freitas et al 2018).…”
Section: Management Of Soil Nutritionmentioning
confidence: 99%
“…Nickel can enhance the resistance of soybeans to Phakopsora pachyrhizi [63]. Nickel (Ni) level and growth, photosynthesis, and physiological and biochemical properties, have potential applications in the phytoremediation of Ni through the application of salicylic acid [64]. When combined with BM + BN + BA, it has been shown that the combination of F2 (5BM + 2BN + 1BA) or G2 (1BM + 2BN + 1BA) can maintain plant height, leaf number, leaf length, leaf width and reduce the severity index.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its status as an essential nutrient for the growth and development of several higher plants (Siqueira Freitas et al, 2018), elevated Ni concentration in soil adversely affects plants (Jiang et al, 2019), animals, and humans (Das et al, 2019;Genchi et al, 2020). Accumulation of Ni in plant tissue is detrimental to agricultural product quality, leading to the disruption of chemical and biological activities in the human body (Olafisoye et al, 2020;Sreekanth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%